Auto-extinction of engineered timber: Application to compartment fires with exposed timber surfaces. (July 2017) - Bartlett, Alastair I.; Hadden, Rory M.; Hidalgo, Juan P.; Santamaria, Simón; Wiesner, Felix; Bisby, Luke A.; Deeny, Susan; Lane, Barbara
Abstract: A series of compartment fire tests with multiple exposed timber surfaces have been undertaken to explore the effect of exposed timber on the fire dynamics and the potential for auto-extinction. A test with exposed wall and ceiling achieved auto-extinction after approximately 21 min. Firepoint theory is applied using temperature data at the charline, is shown to predict a mass loss rate dropping below the critical value at 20–21 min, and thus is successful in predicting auto-extinction. Additional uncertainties caused by delamination are explored, and recommendations for the use of auto-extinction in design are given.